A Study on Tourism Awareness and Satisfaction in Tamil Nadu with Special Reference to Mamallapuram - Ramachandran, A.; Karthikeyan, G.B.; Kavitha, N. (Indian Journal of Marketing, 2008)
Tourism is the fastest growing industry in the world. Tourism needs to be marketed, just as any other product indeed more so, because it is an industry in which the customer still has an immense variety of choice. However, the marketing of tourist destination differ in some important respects from the marketing of other goods and services and an awareness of these differences is important in a successful promotion of the images of tourist places. Like the normal consumer product or service, the tourist product may be seen as a composite product, as an amalgam of attractions, transport, accommodation, and of entertainment. Although general principle of marketing of product of other industries could be applicable to marketing of tourist product, with certain differences in approach. These differences are because of the peculiar features of the tourist product like intangibility, inseparability, variability and perishability.